Um estudo sobre práticas de numeramento na educação do campo: tensões entre os universos do campo e da cidade na educação de jovens e adultos - Kyrleys Pereira Vasconcelos (2011)
In this work, we analyze numeracy practices that are constituted in mathematics education situations occurred in rural schools. These practices are taken as part and reflection of tensions between urban and rural worlds. The empirical material that was analyzed is composed by narratives and transcriptions of interactions, based on the registers of math classes in a Youth and Adult primary school of a land reform settlement, and other registers of interviews and situations of daily life in the settlement. Our analysis highlights: tensions involved in the composition of a curriculum to rural adult education, concerned to the confrontation between demands and discourses proposing a different design based on peasant life and labor with the land, by one side, and the school system structure, based on urban values, in the other side; tensions that are established in numeracy practices experienced by adult students of rural education related to the confrontation between a perspective of mathematical knowledge as universal and a project of using mathematical knowledge in a more pragmatic and local levels; tensions caused by the silencing imposed by the school context to everyday practices of peasant students.